JUN is important for ocular hypertension-induced retinal ganglion cell degeneration - Syc-Mazurek, Stephanie B (Cell Death Dis, 2017)
Ocular hypertension, a major risk factor for glaucoma, is thought to trigger glaucomatous neurodegeneration through injury to retinal ganglion cell (RGC) axons. The molecular signaling pathway leading from ocular hypertension to RGC degeneration, however, is not well defined. JNK signaling, a component of the mitogen-activated protein kinase (MAPK) family, and its canonical target, the transcription factor JUN, have been shown to regulate neurodegeneration in many different systems. JUN is expressed after glaucoma-relevant injuries and Jun deficiency protects RGCs after mechanical injury to the optic nerve. Here, we tested the importance of JNK–JUN signaling for RGC death after ocular hypertensive axonal injury in an age-related, mouse model of ocular hypertension. Immunohistochemistry was performed to evaluate JUN expression in ocular hypertensive DBA/2J mice. JUN was expressed in a temporal and spatial pattern consistent with a role in glaucomatous injury. To determine the importance of JUN in ocular hypertension-induced RGC death, a floxed allele of Jun and a retinal expressed cre recombinase (Six3-cre) were backcrossed onto the DBA/2J background. Intraocular pressure (IOP) and gross morphology of the retina and optic nerve head were assessed to determine whether removing Jun from the developing retina altered IOP elevation or retinal development. Jun deficiency in the retina did not alter DBA/2J IOP elevation or retinal development. Optic nerves and retinas were assessed at ages known to have glaucomatous damage in DBA/2J mice. Jun deficiency protected RGC somas from ocular hypertensive injury, but did not protect RGC axons from glaucomatous neurodegeneration. Jun is a major regulator of RGC somal degeneration after glaucomatous ocular hypertensive injury. These results suggest in glaucomatous neurodegeneration, JNK–JUN signaling has a major role as a pro-death signaling pathway between axonal injury and somal degeneration.